Development of an accessible and low-cost micro-fluidic system (lab-on-a-chip) for detecting circulating breast cancer tumor cells - Valdivia-Silva, Julio (2020)
Objective: to develop a microfluidic system (lab-on-a-chip) for detecting circulating breast cancer tumor cells. Materials and methods: the device was designed using 3D technology, and it was manufactures using soft photolithography and a laser cutting machine. The system performance and its magnetic settings were assessed using Jurkat cells and breast cancer cells that show different expression of CD45 and EpCAM surface markers. Antibodies against these markers were bound to magnetic pellets. Additionally, iron nanoparticles were used for assessing their entrapment. Results: nanoparticles were significantly trapped in the area set by magnetic field modeling. Tumor cells labeled with magnetic antibodies became trapped. Conclusions: we were able to manufacture a lab-on-a-chip system that is capable to trap circulating breast cancer tumor cells, which may become an excellent tool for diagnosis and follow-up for this condition.